Analisis Kelayakan Finansial Pembesaran Udang Vaname (Litopenaeus vannamei) Sistem Intensif - Sitti Zaenab Agustina; Ilham; Andi Rusdi Walinono (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to evaluate the financial aspects of vaname shrimp farming (Litopenaeus Vannamei) with intensive methods at CV Megah Prima Agronusa. The research was conducted with a quantitative descriptive approach, using primary data from field observations and additional data from the literature. Indicators used for financial feasibility analysis include income, BEP (Break-even Point), R/C Ratio (Return on Investment Ratio), ROI (Cost Income Ratio), and PP (Payback Period). The findings of this study indicate that vaname shrimp farming with intensive system in CV Megah Prima Agronusa is financially feasible to do. This can be seen from the total income that reached Rp 1. 300. 947. 352, while the total revenue is Rp 5. 498. 214. 400 and total production costs reached Rp 4.197.267.048. The BEP value in Rupiah is Rp 1. 674. 066. 423, while the BEP in number of units was 23. 197 kg. The R/C Ratio obtained is 1. 30, which indicates that this business is feasible because it is greater than 1. The ROI obtained is 63%, which indicates that this business is appropriate because the standard ROI common in companies ranges from 15% to 25%. The resulting payback period is 1.58, meaning the time required to recoup the investment is 1 year, 5 months, and 8 days. This indicates the business is viable, as the standard payback period for real businesses, including agribusinesses, ranges from 3 to 5 years.